Networked resilience : moving the Asia-Pacific forward - Cook, Alistair David Blair (2014)
As the United Nations moves towards cementing a Post-2015 agenda with the Sustainable Development Goals, how can Asia-Pacific states best achieve these? It is time to recognise our resources from across society to build stronger communities and more resilient states.